2016
DOI: 10.1002/pi.5255
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated polymerization in ionic liquids and its application

Abstract: Ionic liquids (ILs) are low-melting organic salts often liquid at room temperature, whose unique properties are the reason of increasing interest for their applications as solvents, reaction media and functional additives. The exceptional properties of ILs have proved to be particularly useful in polymer science giving the potential to produce polymeric materials with improved properties or to immobilize ILs in polymer matrices while keeping their special characteristics. One of the possibilities is polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 161 publications
(219 reference statements)
1
34
0
Order By: Relevance
“…[28][29][30] Different di-styrenic bisimidazolium monomers were obtained by alkylationof1 -(4-vinylbenzyl)-1 Himidazole with different a,w-bisbromoalkanes (n = 2, 4, and 6 for 1-3,r espectively,S cheme SI.1 in the Supporting Information). The polymeric backbone adequately modified with IL-like moieties (supported IL-like phases,S ILLPs)w as not justa ni nert support fort he dye but controlled the accessibility of reagents/substrates to the active sites and provided specific microenvironmentsf or the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] Different di-styrenic bisimidazolium monomers were obtained by alkylationof1 -(4-vinylbenzyl)-1 Himidazole with different a,w-bisbromoalkanes (n = 2, 4, and 6 for 1-3,r espectively,S cheme SI.1 in the Supporting Information). The polymeric backbone adequately modified with IL-like moieties (supported IL-like phases,S ILLPs)w as not justa ni nert support fort he dye but controlled the accessibility of reagents/substrates to the active sites and provided specific microenvironmentsf or the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The room temperature ionic liquids (ILs) are emerging as green solvents for polymerization reactions and other chemical and biochemical reactions due to their unique physical and chemical properties. The ILs such as [bmim][PF 6 ] and [bmim][BF 4 ] are the commonly used solvents for most free radical polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported the free − radical polymerization of acrylamide catalyzed by water − soluble metalloporphyrins in the presence of β − diketones in an organic and organized reaction media. [24] The room temperature ionic liquids (ILs) are emerging as green solvents for polymerization reactions [25][26][27][28][29] and other chemical and biochemical reactions [30,31] commonly used solvents for most free radical polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration of the polymerization is associated with the increased propagation rate coefficients and reduced termination rate coefficients. 34 Somewhat different situation takes place in the thiol-ene photopolymerization, where in the case of a divinyl ether/dithiol system ILs accelerates the polymerization but the reaction is slower in ILs than in organic solvents. 35 A special case are IL monomers, in which the IL moiety and the polymerizable function are linked together; especially strong development in research is observed for new materials based on such monomers.…”
Section: Ionogelsmentioning
confidence: 99%
“…32 Applications of ionogels include electrolytic membranes (with solid electrolytes), catalytic membranes, drug delivery systems and others. 33,34 Most often the radical polymerization of (meth) acrylates in ILs gives increased polymerization rates and higher molecular weights and yields that that in conventional organic solvents or in bulk. Acceleration of the polymerization is associated with the increased propagation rate coefficients and reduced termination rate coefficients.…”
Section: Ionogelsmentioning
confidence: 99%